Biophysical, Spatial, Functional, and Constructive Analysis of the Pre-Hispanic Terraces of the Ancient City of Pisaq, Cusco, Peru, 2024 - Francis Huaman; Doris Esenarro; Jesus Prado Meza; Jesica Vilchez Cairo; Carlos Vargas Beltran; Crayla Alfaro Aucca; Cecilia Arriola; Valeria Peña Calle (Heritage)
The aim of the research is to examine the biophysical, spatial, functional, and structural components of the pre-Hispanic terracing systems located in the ancient city of Pisaq, considering the impacts of tourism, geological instability, and cultural loss on the ecological and economic value of the terracing system. The methodology includes site analysis, climatology, and an examination of local flora and fauna, supported by digital tools such as QGIS 3.34, Google Earth Pro 2024, and Sun-Path. The results were primarily supported by the use of software tools such as QGIS, AutoCAD 2023, SketchUp 2022, 3D Sun-Path, D5 Render 2024, and Photoshop 2021. The findings include a biophysical analysis related to ecological and economic zoning (EEZ), which determines variables for preservation and reforestation; a spatial analysis measuring the cultivation terraces, with areas ranging from 4.89 ha to 110.20 ha; a functional analysis examining geophysical aspects such as seismic resistance and microclimate effects due to the greenhouse effect; and a constructive analysis that characterizes terrace typologies from an architectural perspective. In conclusion, this analysis evaluates the terracing system of the archaeological park to ensure its preservation and effective management. It also highlights that Inca culture has left a legacy of sustainable architecture, which aligns with the current Sustainable Development Goals (SDGs) (6, 11, 13, 15).